An Inquiry into Cities and Their Role in Subnational Economic Growth in South Africa - Wim Naude; W.F. Krugell (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2004)
South Africa is characterized by significant inequality in spatial economic activity. Whether future growth and development on a subnational level in South Africa will be such as to reduce this inequality may depend on the economic growth and development of South Africa?s largest cities. Our local economic growth empirics show some indications of conditional convergence in output between poorer towns as well as overall between all cities and towns. Between 1990 and 2000 some limited sigma convergence was found but this was driven by declines in the standard deviation of per capita income amongst the poorest quintile of towns. An estimate of conditional beta convergence of 1.2 percent over the period 1990-2000 confirms that overall convergence has been taking place. From an estimation of the determinants of economic growth on a local level, using a dataset on 353 local areas in South Africa between 1990-2000 we found the most significant determinants to be stocks of human capital and distance from harbours and markets. The effect of human capital on economic growth was strongly associated with the presence of large cities, as one would predict from endogenous growth theory.
Keywords: 330; convergence; spatial economic development; South Africa